SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PREWEDDING MENGGUNAKAN METODE WEIGHT PRODUCT - Syahputra, Muhammad Riza; Winanjaya, Riki; Okprana, Harly (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Marriage is the most awaited moment for everyone. Prawdding is an important thing to do before a wedding. Because prewedding photos become the latest trend for photos that will be displayed during the wedding. But in a lot of prewedding photos brides who are not satisfied with the results of these prewedding photos. This system can facilitate the bride and groom in choosing the location of prawedding photos without the need to meet in person to consult. This decision making system is made using the Weight Product method and is made with the php programming language and MySQL database. The WP method is used to find optimal alternatives from a number of alternatives. The selection of the location of the prewedding photo uses weighting for each criterion. The bride and groom can choose the desired location based on criteria such as the number of spots, themes, location distance, number of shoots with weights determined by the user based on the level of importance. The results of this system are displaying praweding locations based on the location of prawedding photos that can be ordered by the bride and groom. The selection of prewedding photo locations can be done optimally so that the results of the decision are as expected.Keywords: Decision Support System, Prewedding Location, Product Weight